Efek Perubahan Cuaca Terhadap Grafik Kenyamanan Termal Kamar Kos - Nagata, Krisna Wijaya (Unika Santo Thomas, 2024)
Weather changes are currently unpredictable due to increasing global warming, this will affect thermal comfort in buildings. In this case, the boarding room is used as a place of rest as well as activities should have comfort so the need for experimental quantitative research to discuss how the effect of weather changes on thermal comfort in the boarding room and how if associated with thermal comfort standards according to SNI and Ministry of Health. On the other hand, this research is expected to be able to provide references for further researchers and add reading material for peer groups. From the results of this study revealed that the weather greatly affects the thermal comfort in the building, from four days showed anomalous changes in air temperature and relative humidity in the building. The combination of air temperature and relative humidity in the boarding room is not one in the thermal comfort standards of SNI and the Ministry of Health because of the anomalies that occur as well as factors such as wall materials that absorb heat and the lack of ceiling height causes heat trapped in the boarding room.